Peningkatan Hasil Belajar Ipa Materi Bencana Alam Dan Mitigasi Bencana Dengan Pendekatan Blended Learning Melalui Google Classroom - Rusman Saleh, Nasia (Al-Khazini: Jurnal Pendidikan Fisika, 2022)
Abstrack. The emergence of a pandemic outbreak in 2020 forced us to carry out social activities. Included in face-to-face at school so that learning must be held boldly. One application that can be used in bold learning is Google Classroom using a blended learning approach. The advantage of the Google Classroom application compared to other applications is that the Google Classroom application can be used to create and manage classes, assignments, and can provide direct input. The formulation of the research problem is whether there is an increase in science learning outcomes for natural disasters and disaster mitigation with a blended learning approach through Google Classroom students of class X Accounting and Finance Institution 2 SMK Negeri 1 Tarakan. The aim of the research is to improve learning outcomes of natural disaster and disaster mitigation science learning with a blended learning approach through google classroom for students of class X Accounting and Finance Institution 2 SMK Negeri 1 Tarakan. This research is a classroom action research (Classroom Action Research) with four activities, namely action planning, implementation, observation, and reflection. The reason for choosing CAR is because it can improve teacher performance so that they become professional. Data collection techniques were carried out by giving tests to students and observing the activities of teachers and students carried out by an observer. Based on the results of the study, the classical average of students' learning mastery in Cycle I was 73.24 and in Cycle II it increased to 83.24, as well as observing student activities that increased and all aspects were categorized very well. From the results of this study, learning science on disaster and natural disaster mitigation materials with a blended learning approach in the Google Classroom application can improve the learning outcomes of students in class X Accounting and Finance Institution 2 SMK Negeri I Tarakan. Keywords: Blended learning, Google Classroom